2022
DOI: 10.3390/diagnostics12112697
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation and Application of Confocal Laser Endomicroscopy in Brain, Head and Neck Surgery—A Review

Abstract: When we talk about visualization methods in surgery, it is important to mention that the diagnosis of tumors and how we define tumor borders intraoperatively in a correct way are two main things that would not be possible to achieve without this grand variety of visualization methods we have at our disposal nowadays. In addition, histopathology also plays a very important role, and its importance cannot be neglected either. Some biopsy specimens, e.g., frozen sections, are examined by a histopathologist and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Confocal laser endomicroscopy (CLE) represents a promising technology that provides the real-time histological visualization of living tissue [128,129]. In this context, CLE is an encouraging tool to obtain near real-time intraoperative histological data in neurosurgery.…”
Section: Future Directions-digital Biopsymentioning
confidence: 99%
“…Confocal laser endomicroscopy (CLE) represents a promising technology that provides the real-time histological visualization of living tissue [128,129]. In this context, CLE is an encouraging tool to obtain near real-time intraoperative histological data in neurosurgery.…”
Section: Future Directions-digital Biopsymentioning
confidence: 99%
“…Through advances in biophotonics, pCLE technology has been developed, which has made it possible to directly examine tissue at a microscopic scale during open surgery. Preliminary studies have shown that pCLE can help identify residual cancer tissue, leading to higher rates of tumor B Chi Xu chi.xu20@imperial.ac.uk Alfie Roddan a.roddan21@imperial.ac.uk Haozheng Xu haozheng.xu19@imperial.ac.uk Giannarou Stamatia stamatia.giannarou@imperial.ac.uk 1 Hamlyn Centre for Robotic Surgery Department of Surgery and Cancer, Imperial College London, London SW7 2AZ, UK removal [1,2]. To obtain high-quality pCLE data, it is necessary to keep the probe at an optimal working distance of micrometer scale [3,4]and perpendicular to the tissue surface [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the above, there is an important research emphasis on advanced intra-operative tissue differentiation techniques. This can be either point based, e.g., Raman and reflectance spectroscopy (Vaqas et al, 2018 ), endomicroscopy (Kakaletri et al, 2022 ), or wide field, e.g., multispectral (MSI) or hyperspectral (HSI) imaging (Shapey et al, 2019 ). HSI in particular has already been shown to be a promising tool, demonstrating the capability to facilitate real-time wide-field label-free intra-operative tissue differentiation (Fabelo et al, 2018 , 2019 ; Shapey et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%